2023
DOI: 10.3390/jmse11101948
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Monitoring System for the Force Characteristics of Floating Bollards in a Ship Lock

Linjian Wu,
Jia Yang,
Zhouyu Xiang
et al.

Abstract: Due to the large scale of navigation ships, the fast speed of entering the lock, and the irregular mooring and the complicated flow conditions in the lock chamber, it is common for the floating bollards of the lock to suffer structural damage or even failure due to the overloaded mooring force. However, the traditional cable load measurement method cannot offer real-time feedback on force characteristics of floating bollards, making it difficult to accurately judge its service status. To this end, according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To better understand bollard resistance and their ability to withstand damage under varying dynamic loads a variety of research projects have been undertaken. Wu et al [13] discussed the shortcomings of conventional cable load measurement techniques for floating bollards highlighting the requirement for immediate feedback on the properties of force. The study uses 3D finite element simulations to determine theoretical model parameters for a floating bollard load response using data from a representative ship lock project in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand bollard resistance and their ability to withstand damage under varying dynamic loads a variety of research projects have been undertaken. Wu et al [13] discussed the shortcomings of conventional cable load measurement techniques for floating bollards highlighting the requirement for immediate feedback on the properties of force. The study uses 3D finite element simulations to determine theoretical model parameters for a floating bollard load response using data from a representative ship lock project in China.…”
Section: Introductionmentioning
confidence: 99%
“…In a field test, it creates an intelligent monitoring system that integrates big data the internet and cloud services and shows accuracy. According to the previous study [13], ship lock automation and general risk prevention can be improved by implementing a digital perception monitoring platform. Pin et al [14] suggested a novel approach for monitoring mooring bollard structural safety.…”
Section: Introductionmentioning
confidence: 99%